COGNITIVE IMPAIRMENT DETECTION IN ADULT THALASSEMIA PATIENT USING MOCA-INA - Wardoyo, Chandra Calista; Gamayani, Uni; Ong, Anam; Rizal, Ahmad; Wibisono, Yusuf; Amalia, Lisda; Panigoro, Ramdan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Background: Cognitive impairment in thalassemia patients are prevalent, therefore early detection of cognitive impairment in adult thalassemia patients is crucial for prevention. Montreal Cognitive Assessment (MoCA) is a public domain cognition screening tools that covers all cognitive domains in detecting mild cognitive impairments.Objective: To compare cognitive function between adult thalassemia patients and healty control by using Indonesia version of MoCA test (MoCA-Ina)Methods: This prospective observational analytic with case control study, compared the total scores and scores of each domain of cognition between adult thalassemia patients and healthy subjects at the Medical Hematology Oncology Clinic of Dr. Hasan Sadikin General Hospital, Bandung, Indonesia using MoCA-Ina from August to October 2018.Results: A total of 32 thalassemia subjects and 50 healthy subjects were conducted. A total of 16(50%) subjects in the case group had a value of MoCA-Ina <26, while only 1(2%) healthy control had a value of MoCA-Ina <26. The median total MoCA-Ina score in case and control groups were 25.5 and 27.50 (p <0.001). The median score of memory domains, executive functions and visuospatial of the case and control groups were 3 versus 4 (p <0.001), 3 versus 3.5 (p <0.001) and 3.53 Â± 0.671 versus 3.88 Â± 0.385 (p <0.003), respectively.Conclusion: Adults thalassemia patients have lower score in total MoCA-Ina, domains of memory, executive function and visuospatial score compared to healthy control.